Poverty and inequality in Francophone Africa, 1960s–2010s. Issue 1 (2nd January 2021) - Boukaka, Sédi-Anne; Mancini, Giulia; Vecchi, Giovanni
ABSTRACT: The paper provides first generation estimates of poverty and inequality rates for three countries in Francophone Africa – Cameroon, Côte d'Ivoire, and Gabon – in the aftermath of independence. Sources – a large collection of historical household budgets – are new, as is the method that allows to connect historical sources to modern household budget surveys, and to deliver nationally representative estimates. The second part of the paper identifies the trend of poverty and inequality in Côte d'Ivoire for the years 1965 to 2015: mean income growth failed to reduce poverty during the 15 years of economic boom post-independence (1965–1979) because of increasing inequality. Conversely, in the following period (1979–2015) poverty changes are mostly guided by the evolution of growth.